1992
DOI: 10.1139/v92-258
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of L-rhamnose and D-mannose by Cr(VI) in perchloric acid. A comparative study

Abstract: LUIS F. SALA, SANDRA R. SIGNORELLA, MARCELA RIZZOT~O, M A R~A I. FRASCAROLI, and FABIO GANDOLFO. Can. J. Chem. 70, 2046Chem. 70, (1992.The oxidation of L-rhamnose and D-mannose by Cr(V1) in perchloric acid follows the rate law: M -~ S-I pour le L-rhamnose. Cette equation de vitesse correspond a la reaction conduisant a la formation de la L-1 ,4-rhamnonelactone et de la D-1 ,4-mannonelactone. I1 ne se produit pas de clivage en dioxyde de carbone lorsque la quantite d'aldose utilisee depasse de 20 fois ou pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 10 publications
4
35
0
Order By: Relevance
“…[2]). This is based on the mechanism reported for aldoses, which are also selectively oxidized by Cr VI at the hemiacetalic group with an initial two-electron transfer slow step (21)(22)(23)(24)(25)(26)(27)(28). After the slow redox step, Cr IV is predicted to react with excess saccharide to yield Cr III and a disaccharide radical in a fast step (eq.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…[2]). This is based on the mechanism reported for aldoses, which are also selectively oxidized by Cr VI at the hemiacetalic group with an initial two-electron transfer slow step (21)(22)(23)(24)(25)(26)(27)(28). After the slow redox step, Cr IV is predicted to react with excess saccharide to yield Cr III and a disaccharide radical in a fast step (eq.…”
Section: Discussionmentioning
confidence: 92%
“…Our studies on the reduction of Cr VI and the intermediate Cr V by aldoses (21)(22)(23)(24)(25)(26), deoxyaldoses (27)(28), sugar acids (31,32,35), and methyl glycosides (29)(30) showed that the relative redox reactivities of these saccharides toward chromate are based on the relative rates of the oxidation vs. complexation processes. In view of some preliminary results obtained on the milk-Cr VI system suggesting the formation of long lived lactose-Cr V species generated by direct reaction of Cr VI with lactose (5), we decided to evaluate the kinetics of the reaction of Cr VI with four disaccharides: D-lactose (Lac), D-maltose (Mal), D-cellobiose (Cel), and D-melibiose (Mel), to determine the influence of the glycoside moiety attached to the C 6 or C 4 of glucose (glc) on the chelating and (or) redox reactivity of the saccharide with high oxidation states of chromium.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…(ii) Paper Chromatography [18]. Generally, paper chromatographic technique is used to identify the oxidation products of carbohydrates.…”
Section: Product Identification Andmentioning
confidence: 99%